2020
DOI: 10.3390/ijerph17093298
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Satisfaction with Care Services among Family Members of Older Adult Residents of Long-Term Care Facilities

Abstract: This study identified predictors of satisfaction with care services among family members of older adults residing in long-term care facilities (LTCFs). In this cross-sectional descriptive study, the participants were 330 family members of older adult residents of LTCFs in Seoul, Gyeonggi, Gangwon, Gyeongbuk, and Chungnam, Korea. Data were collected from July to October 2018 using a structured self-report questionnaire. Data were analyzed using descriptive statistics, independent t-testing, one-way ANOVA, Krusk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…2.1.2 Staff. Several prior studies determined that staff play a crucial role in affecting resident satisfaction (Chou et al, 2001;Chou et al, 2003;Lee, 2020aLee, , 2020bPark and Sok, 2020;Song and Jang, 2020). CCRCs have various types of staff, including but not limited to personal care aides, food preparation workers, housekeeping, receptionists and information clerks and management assistants (Jeste and Childers, 2017).…”
Section: Literature Review 21 Factors Affecting Ccrc Resident Satisfa...mentioning
confidence: 99%
See 3 more Smart Citations
“…2.1.2 Staff. Several prior studies determined that staff play a crucial role in affecting resident satisfaction (Chou et al, 2001;Chou et al, 2003;Lee, 2020aLee, , 2020bPark and Sok, 2020;Song and Jang, 2020). CCRCs have various types of staff, including but not limited to personal care aides, food preparation workers, housekeeping, receptionists and information clerks and management assistants (Jeste and Childers, 2017).…”
Section: Literature Review 21 Factors Affecting Ccrc Resident Satisfa...mentioning
confidence: 99%
“…To create a sense of community and a sense of home, CCRCs have incorporated many hospitality attributes into their design and decorations (Johs-Artisensi et al , 2021; Vitale-Aussen and Andrews, 2016), such as decorating a dining room like a restaurant (Negrea, 2016). Some studies anchored that the design is also seen to be a necessary aspect that affects resident satisfaction (Chou et al , 2003; Lee, 2020a, 2020b; Nordin et al , 2017; Song and Jang, 2020). Song and Jang (2020) found that the physical housing environment and facility size were predictors of resident satisfaction.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Elle est l'un des critères de succès les plus importants et un atout majeur pour le développement d'une bonne relation entre un usager et le médecin [1]. La recherche constante de cette la satisfaction a conduit à beaucoup d'étude à travers le monde [2][3][4][5][6][7][8][9][10]. Une étude menée en France au CHU de Sens par Renaut en 2000 notait que 91% des patients étaient satisfaits de leur hospitalisation [11].…”
Section: Introductionunclassified